ANALYSIS OF COMMUNICATION PATTERNS BETWEEN TEACHERS AND STUDENTS ON THE LEARNING DISCIPLINE OF MADRASAH IBTIDA'IYAH STUDENTS - Rindi Yanika Maryanti; Arifin, Moch. Bahak Udin By (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
It is found in many educational institutions in big cities and small towns or inland, especially at the elementary school or Madrasah Ibtida'iyah level, that students are predominantly undisciplined in carrying out their obligations as students. This problem is further strengthened by the teacher's communication pattern, which is not implemented intensively and maximally evenly with students, making students undisciplined in carrying out all their obligations. Therefore, the researcher's aim in taking this topic is to discover how the communication patterns between teachers and students correlate with learning discipline and how effective teacher-student communication is with student learning discipline. In this research, the researcher used a quantitative descriptive approach to find answers to the discussed problems using the prerequisite, validity, reliability, and normality tests. To find out the relationship between communication patterns and discipline, researchers used a simple correlation test, and to find out how effective communication was on discipline, researchers used regression analysis. After the teacher and student questionnaires have passed several tests, the questionnaire statement sheet is obtained and outlined with the results of calculations from the research that has been carried out, that the communication patterns established by teachers with students have a close relationship in improving the learning discipline of elementary school students. It can be concluded that by establishing effective, maximal, and intense communication, teachers can improve students' learning discipline and obtain learning results that align with each lesson's expectations and objectives.